PENGARUH PEMBERITAAN COVID-19 DI MEDIA ONLINE TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT MAHASISWA FISIP UDA 2018 - Yosua Putra Valentino; Besti Rohana Simbolon (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2020)
This research entitled "The Influence of COVID-19 News in Online Media towards the Clean and Healthy Living Behavior of FISIP UDA Students 2018". This research aims at finding out the effectiveness of COVID-19 News in Online Mass Media in influencing Clean and Healthy Living Behaviors seen from aspects of Attention, Interests, Desires, Decisions and Actions / Behaviors of FISIP University of Darma Agung Students class of 2018. The population in this study is students of FISIP University of Darma Agung class of 2018 as many as 110 peoples consisting of two studies, namely Communication Science and Government Science. And then sampled using the Slovin formula into 33 respondents. Then a single table analysis and cross-table are performed to find out how respondents judge both variables. Furthermore, hypothetical testing was conducted to find out the relationship between covid-19 variables in online mass media and student clean and healthy behavior variables analyzed using spearman correlation formula. The correlation results looking at COVID-19 News in Online Mass Media towards Clean and Healthy Living Behavior obtained a significance value of 0.002 which means both variables are significant to each other. From the hypothetical test results obtained rho = 0.511 defines that the positive correlation, means that the higher the assessment rate of COVID-19 News In Online Media then Clean and Healthy Living Behavior is also improving. This rho value is also included in the category that is quite meaningful so that covid-19 news in online media can be quite affecting in the Clean and Healthy Living Behavior of FISIP Students of Darma Agung University class of 2018. Through covid-19 news in online mass media, it is able to influence the clean and healthy living behavior of FISIP Students of Darma Agung University 2018 to overcome the spread of pandemic diseases caused by covid-19 virus.